2014
DOI: 10.1073/pnas.1403657111
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the benefits of vehicle pooling with shareability networks

Abstract: Taxi services are a vital part of urban transportation, and a considerable contributor to traffic congestion and air pollution causing substantial adverse effects on human health. Sharing taxi trips is a possible way of reducing the negative impact of taxi services on cities, but this comes at the expense of passenger discomfort quantifiable in terms of a longer travel time. Due to computational challenges, taxi sharing has traditionally been approached on small scales, such as within airport perimeters, or wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
540
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(546 citation statements)
references
References 21 publications
4
540
0
2
Order By: Relevance
“…Another investigation for taxi ridesharing in New York City (Ota, Vo, Silva, & Freire, 2015) identified 46% and 61% savings, respectively, in taxi trips if rides are shared among two and three passengers with nearby trips within 1.6 kilometers. Using the same algorithm for analysis of taxi ridesharing potential proposed by Santi et al (2014), Tachet et al (2017) showed that ridesharing benefits follow the same trends in San Francisco, Vienna and Singapore with total number of taxi trips reduced by 50% for San Francisco and Singapore, and by 42% for Vienna.…”
Section: Recent Findings On Ridesharing Potentialmentioning
confidence: 90%
See 2 more Smart Citations
“…Another investigation for taxi ridesharing in New York City (Ota, Vo, Silva, & Freire, 2015) identified 46% and 61% savings, respectively, in taxi trips if rides are shared among two and three passengers with nearby trips within 1.6 kilometers. Using the same algorithm for analysis of taxi ridesharing potential proposed by Santi et al (2014), Tachet et al (2017) showed that ridesharing benefits follow the same trends in San Francisco, Vienna and Singapore with total number of taxi trips reduced by 50% for San Francisco and Singapore, and by 42% for Vienna.…”
Section: Recent Findings On Ridesharing Potentialmentioning
confidence: 90%
“…He, Hwang and Li (2014) found that increasing the number of riders to eight per vehicle, by using a mini van, would increase overall travel savings up to 60%. In an investigation for taxi ridesharing in New York City, Santi et al (2014) concluded that, with waiting time not exceeding 5 minutes, ridesharing with two or three passengers could reduce total taxi trips by 50% (reaching full potential in trip reduction) and 60%, respectively. This equates to about a 40% reduction in total taxi trip length.…”
Section: Recent Findings On Ridesharing Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…high-speed broadband networks) and can stimulate private investment in the short term" (OECD, 2016, S. 46 Für eine detaillierte Studie der möglichen Verbrauchervorteile durch den Eintritt neuer Anbieter im Markt für urbane Mobilität vgl. , Santi et al (2014) sowie Cramer und Krueger (2014). 25 Das von Kritikern einer Reform der Taxi-Regulierung oft vorgebrachte Argument der Informationsasymmetrie zwischen Fahrern und Fahrgästen (vgl.…”
Section: Geschäftsmodelle Der Sharing Economyunclassified
“…The excellent paper of Santi et al (2) addresses one of the new forms of consumption that could help in reaching this goal. Santi et al's report shows the feasibility of a shareable taxi service in New York City and its benefits: reduction in cost of service, total travel time, trips, vehicular traffic congestion, and air pollution.…”
mentioning
confidence: 99%